Comparative evaluation of serum C-reactive protein levels in chronic and aggressive periodontitis patients and association with periodontal disease severity - Goyal, Lata (Contemp Clin Dent, 2014)
OBJECTIVE: C-reactive protein (CRP) is an acute-phase reactant and has been proved to be a significant predictor of future cardiovascular events. Recent studies have demonstrated a correlation between periodontitis and elevated CRP levels. However, most of the studies have focused on chronic periodontitis and very few studies are done in patients with aggressive periodontitis. The aim of this study was to determine and compare the relative levels of serum CRP in aggressive and chronic periodontitis patients. MATERIALS AND METHODS: A total of 75 systemically healthy subjects were divided into three groups: Group I, nonperiodontitis subjects; group II, chronic generalized periodontitis patients and group III, generalized aggressive periodontitis patients. All participants were subjected to quantitative CRP analysis using enzyme-linked immunosorbent assay. RESULTS: Mean CRP levels were significantly greater in both group II and III as compared to group I and group III having greater level than group II. Furthermore, CRP levels positively correlated with the amount of periodontal destruction as measured by probing depth and clinical attachment loss. CONCLUSION: The present study indicates a positive correlation between CRP and periodontal disease severity with particular concern in younger individuals that could be a possible underlying pathway in the association between periodontal disease and the observed higher risk for cardiovascular disease in periodontitis patients.